IMPLEMENTASI METODE NEWSBOY PROBLEM PADA BEAU BAKERY DI JAKARTA - Meilany Anggela Ayu V.; Antonius Budhiman Setyawan; Juliani Dyah Trisnawati (Perpustakaan Universitas Surabaya, 2018)
Application of inventory control is aimed support bakery owner’s decision making in order to obtain optimum inventory and optimum production quantity in the lO best-selling products, namely Burger Buns Milk, Soft Pretzel Regular, Soft roll Cranberry, Walnut cranberry, Baguette Viennoise, Hot Dogs Charcoal, Olive focaccia, Rectangular multigrain. Application of inventory control was necessary because the bakery didn’t get the maximum profit and even suffer losses owing can’t determine the optimum inventory levels at the fourth weeks on December 2Ol3 until 2Ol6. In addition, the products are not sold until 2O:OO will also be sold at the residual value or scrap value of 5O% of the sale price initially. The implementation uses the method of calculation of Newsboy Problem or Single Period Problem. The calculations begin from determining the probability sold and cumulative probability. Thereafter, the method applied newsboy problem with the known unit cost, scrap value, and selling price. After getting what the optimal production quantity, expected profit is calculated by using the quantity of information production, sales quantity, scrap value, selling price and unit cost. After getting the calculation using the Newsboy Problem method, it performed the optimal production quantity, optimal inventory levels and expected maximum profit obtained the bakery at the fourth weeks in December when using the method of Newsboy Problem.